Situación ambiental de los residuos sólidos domiciliarios en el asentamiento humano Santa Rosa, distrito de San Juan Bautista, Loreto - Perú, 2022 - Torrejon Alvan, Maria Belen (2022)
The present work of thesis was developed in the Santa Rosa Human Settlement situated at the km 3 on the left side of the highway Santo Tomas, the evaluation was realized during the months of March to July of 2022, and it had had as objective evaluated the environmental situation of the rural villager of the Santa Rosa Human Settlement about the environmental problematic of the household solid waste generated in the developed of their daily activities, and to improve their segregation and disposal. Through the analysis and the processing of the information collected the perception of the rural villager about the household solid waste generated in the Santa Rosa Human Settlement, through the application of a survey, which covers the aspects of knowledge, awareness, management of household solid waste, cover valid information which contribute to plan proposes for a better gestion, segregation, disposal, sensibilization, and conscientization of household solid waste.